Dampak Perkembangan Desa Wisata pada Fungsi Hunian di Desa Bungaya Kabupaten Karangasem - Ni Luh Jaya Anggreni (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2018)
This paper investigates the impacts of the so called community-based tourist development in Bungaya Settlement, a traditional village of Karangasem Regency of Bali Province. It seeks to answer two research questions: 1) how has tourism affected the function of homes in Bungaya?; and 2) what are the dominant forces determining the evolution of homes in Bungaya?. In doing so, the author exercises her understanding of the tourist industry as well as her thorough comprehension of home as a form of shelters and a base for income generation. A mixed qualitative and quantitative research approaches were used, in which on-site observations and interviews were employed for data collection. The study finds many homes have been spatially and architecturally reconfigured to accommodate needs resulted from the community-based tourist development. These reconfigurations are brought by the emergence of new functions and spaces that need to be accommodated by a home; makeover of the outer facades of many homes; resizing of buildings exist within; amendment on the layout of a home; and the use of more updated building materials. Since level of changes varies from one home to another, the study classifies three types of modifications, which are: low, medium and high level. Major driving forces for these levels of modifications and where they take place include: the need for new tourist amenities; requirement to enhance the attractiveness of Bungaya Settlement as a tourist destination; level of accessibility that of each home has to the tourists; and how Bungaya's development has been planned and governed. Keywords: change, function, settlement, tourism, Bungaya Village